A changing pattern of injuries to horse riders. Issue 5 (1st September 2002) - Moss, P S; Wan, A; Whitlock, M R
Abstract : Objectives: To describe the demographics and nature of injuries occurring on or around horses, to examine the nature of protective clothing in relation to these injuries, and to compare our data with previously published work in this area. Methods: Patients were identified using the term "sports injury–horse riding" from the departmental database for one calendar year from February 2000. Data were collected regarding demographics, injuries, protective clothing, and outcome. The data were then analysed and compared with the previously published literature. Results: 260 patients' records were analysed. The patients were mostly young (median age 26) and female (84.6%). The majority of patients had a single injury (88.8%). Seventeen per cent had an isolated head injury, all of which proved to be minor. Multiple injuries including the head accounted for 8.5% of all injuries. These again proved minor, bar one fatality where the helmet came off before impact. Upper limb injuries accounted for 29.2% of all injuries of which 61.8% sustained a fracture of which 36.2% were to the wrist. When compared with previous work the incidence and severity of head injury continues to decline while the relative number and severity of upper limb injuries increases. Conclusions: The majority of head injured riders are wearing approved helmets and sustaining only minor injury. There is currently no protective gear recommended for the upper limb and more specifically the wrist. This paper identifies the potential need for research and development of such protection.